Identification of auxins, gibberellins and cytokinins in raspberry fruits (Rubus idaeus) - Ramírez, Homero; espanol, espanol; espanol, espanol; espanol, espanol; espanol, espanol (Ecosistemas y Recursos Agropecuarios, 2024)
Raspberry is a crop of great demand in recent years in the international market. This distinction is focused on its high content in vitamins A and C, fiber, nutrients such as Ca and Fe, flavonoids and antioxidants. These compounds besides to be as part of aromatic and taste characteristics of the fruit, contribute to the immunology human system strengthening, in particular against diseases such as cancer, diabetes and cardiovascular. Endogenous hormones direct the role of these molecules during growth and development in several horticultural species. In raspberry it is unknown. For this reason, it was investigated their presence in fruits of raspberry cv UANC-2022, using the gas chromatography mass spectrometry technology under a complete randomized design. The following hormones were identified: gibberellins A4, A7, A44 and A53; auxin indole acetic acid and the cytokinin zeatin.